Inspirasi Keadilan Ensiklik “Sollicitudo Rei Socialis” bagi Perjuangan Keadilan di Maluku - Romario Primus Rumlus; Januarius Heatubun (STP Dian Mandala Gunungsitoli Nias Keuskupan Sibolga, 2026)
The encyclical Sollicitudo Rei Socialis highlights the Church's concern about social injustice, particularly the condition of the poor who do not have fair access to resources intended for all. As a development of Populorum Progressio, this document emphasizes the importance of integral development centered on human dignity through the priority of solidarity. This article aims to reactualize the teaching of justice in Sollicitudo Rei Socialis and examine its relevance in the context of Maluku society which still faces social inequality, issues of natural resource management, gender inequality, and post-conflict impacts. The analysis is carried out by combining descriptive methods to explain the concept of justice in the encyclical and reflective-analytical methods to interpret and draw its contextual implications for social reality in Maluku. The results of the study indicate that solidarity is not only an individual moral virtue, but also a transformative principle that encompasses structural and cultural dimensions in communal life. In the Maluku context, solidarity plays a crucial role in encouraging active community participation in addressing injustice and restoring social harmony and interfaith tolerance. Therefore, this article emphasizes that solidarity is a relevant and contextual ethical foundation for realizing social justice and shared prosperity.